Knowledge Levels of Nurses Working in Inpatient Institutions in Erzurum Province Regarding Central Venous Catheter Care - Zuhal PALIOGLU; Gulay IPEK COBAN (Atatürk University, 2021)
Aim: This study was carried out as a descriptive study to determine the knowledge level of nurses that Working in Inpatient Institutions in Erzurum Province about central venous catheter care. Method: The universe of this descriptive study was carried out between June - August 2017 in Palandoken Hospital, Regional Training and Research Hospital and Ataturk University Research Hospital in Erzurum. In addition to this, all of the nurses working in these three hospitals were employed in clinics such as internal medicine, cardiology, neurology, cardiovascular surgery, thoracic surgery, nephrology, dialysis, oncology, intensive care and endocrinology where central venous catheter usage was more frequent were created the universe of this descriptive study. Sampling was not selected in the study and the study was completed with 212 nurses. "demographic information form" and "Knowledge Levels of Nurses on Central Venous Catheter Care" were used for data collection. Data assessment stage was analyzed by using number, percentage and mean of descriptive statistics. For the further analysis, chi squared with four groups and fisher's exact chi squared test were used. Results: In the research results; knowledge levels about CVC care of nurses show a statistically significant difference according to working time of nurses, education level, the departments they work and in-service training (p<0.05). When comparing the knowledge levels of nurses working in different institutions, nurses working in university research hospital were found to have higher levels of knowledge about central venous catheter care than nurses working in state hospitals (p<0.05). Conclusion: It was seen that the shortcomings of the institutions in the field of in-service training and the deficiencies in the material affect the knowledge levels of central venous catheter.